Evaluating multi-satellite chlorophyll-a datasets an ocean colour case study within the Southern Benguela - Oehley, Craig (Department of Biological Sciences, 2026)
Chlorophyll-a (chl-a), a photosynthetic pigment that can be derived from satellite ocean colour, is often used as a proxy for phytoplankton biomass and to derive primary productivity. Initiatives such as the Ocean Colour Climate Change Initiative (OC-CCI) produce merged multi-satellite products to create consistent long-term time-series datasets for climate studies at a global scale. Their ability to handle variable in-water conditions is critical for their mission parameters. This study compares the performance of two European multi-satellite chl-a products, from the OC-CCI and GlobColour projects against a regionally tuned Sentinel-3 product within the Southern Benguela region. The three products were assessed against a collated database of coincident in situ chl-a matchups to derive a series of performance metrics. The regionally tuned Sentinel-3 product outperformed the two global products in terms of Mean Absolute Error but showed a slight consistent overestimation bias. Analysis of match-ups showed an underestimation of high chl-a concentrations and overestimation of lower chl-a concentrations by both global products. An application of the products within St.Helena bay during high biomass bloom events showed that the Sentinel-3 product's ability to capture extreme chl-a concentrations was far higher than both global products. Spatial mismatch between zones of high chl-a concentration also indicate differences in processing chains and flagging techniques.